2022
DOI: 10.3390/ijms23073792
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Acute Kidney Injury: Potential Therapeutic Avenue for Renal Repair and Regeneration

Abstract: Acute kidney injury (AKI) is a sudden decline of renal function and represents a global clinical problem due to an elevated morbidity and mortality. Despite many efforts, currently there are no treatments to halt this devastating condition. Extracellular vesicles (EVs) are nanoparticles secreted by various cell types in both physiological and pathological conditions. EVs can arise from distinct parts of the kidney and can mediate intercellular communication between various cell types along the nephron. Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 210 publications
1
10
0
Order By: Relevance
“…For indirect inspection of 10-day cultured MSCs, their shed MVs were isolated. Characterization of isolated MVs from MSCs, including shape, diameter, and size distribution (Figure 3) was in accordance with previous studies [32,33]. There are few studies about the mRNA, miRNA, and protein contents of MVs.…”
Section: Discussion and Future Remarkssupporting
confidence: 89%
See 1 more Smart Citation
“…For indirect inspection of 10-day cultured MSCs, their shed MVs were isolated. Characterization of isolated MVs from MSCs, including shape, diameter, and size distribution (Figure 3) was in accordance with previous studies [32,33]. There are few studies about the mRNA, miRNA, and protein contents of MVs.…”
Section: Discussion and Future Remarkssupporting
confidence: 89%
“…Xie, et al reported regulation of hematopoiesis by miRNAs in MSCs-derived MVs applied in ex vivo expansion of cord blood mononuclear cells [33]. In another study, MSCs-derived MVs enhanced the survival of renal cells both in vitro and in vivo [32]. Herein some stemness markers such as OCT4 and ALP [34] were evaluated.…”
Section: Discussion and Future Remarksmentioning
confidence: 99%
“…In addition to their therapeutic possibilities, exosomes have also been studied for their potential as biomarkers for the identification of AKI 527 . A research paper titled: “Unconscious Cells and Sudden Kidney Damage: Potential Therapeutic Avenue for Renal Repair and Regeneration” 528 highlighted the effects of exosomes and how they affect multiple pathways of tissue regeneration including their role in (1) attenuating inflammation and improving immune modulation, (2) aiding in cell proliferation, (3) improving oxidative stress, (4) autophagy, and (5) minimizing cell death. Multiple lines of evidence substantiate the renoprotective impact of EVs derived from various sources in mitigating renal injury in diverse experimental models of AKI as presented in Table 16 528 …”
Section: Treatment Of Damaged Organsmentioning
confidence: 99%
“…Exosomes (30–150 nm) originate through the invagination of the limiting membrane of the early endosome, i.e., multivesicular bodies (MVBs) and are released to the extracellular environment upon fusion of MVBs with the plasma membrane [ 5 ]. Microvesicles (MVs) (100–1000 nm) are produced by outward budding and pinching of the plasma membrane [ 8 , 9 ]. The intracellular membrane is not involved during the secretion of microvesicles, and thus the membrane composition closely mirrors that of parent cells, a key difference from exosomes, which are heavily enriched in phosphatidylserine [ 4 ].…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%